Penciptaan Busana Avant-Garde dengan Sumber Ide Dewi Artemis - Mey Surya Mada; Urip Wahyuningsih (BAJU: Journal of Fashion and Textile Design Unesa, 2026)
This study aims to explore the application of manipulating fabric ruffles in avant-garde fashion using Artemis from Greek mythology as the source of inspiration. Artemis was selected due to her representation of strength, independence, and elegance, which aligns with the fundamental principles of avant-garde design. The research employs the Double Diamond Model, consisting of the discover, define, develop, and deliver stages. The design process begins with an exploration of the symbolism and character of Artemis, followed by the development of design concepts through moodboards, silhouette determination, material exploration, and the application of ruffles as the main design element. The final garment is then evaluated by three experts in fashion design. The results indicate that the application of manipulating fabric ruffles successfully creates dynamic volume, texture, and movement, while effectively representing the visual and conceptual character of Artemis. Therefore, this technique is considered effective and appropriate for avant-garde fashion as a medium of innovative and meaningful artistic expression.